Artificial intelligence across industries : how AI is transforming telco, retail, and financial services - Barlow, Mike (Michael Alan) (O'Reilly Media, 2017)
Artificial Intelligence is transforming the world. Through a convergence of technology leaps, social transformations, and genuine economic needs, AI is moving from its academic roots to the forefront of business and industry. In this report, we examine how companies in three economic sectors--telecommunications, retail, and financial services--are tackling new challenges and opportunities by incorporating AI into their products and operations. Every nook and cranny of the modern economy will eventually feel AI's impact, from energy, transportation, and healthcare to manufacturing, entertainment, education, IT, and government. And the boom in AI development will lead to greater demand for hardware and services among growing AI developer communities. As a leader in visual computing technologies, NVIDIA has become a partner for many organizations taking the plunge into AI. This report lists startups and AI use cases in our three target sectors, and helps you explore how: Big data technology fulfilled the promise of previous research into AI Telecommunications companies are using AI to improve and expand high-quality voice and data services Retailers are leveraging their own data to increase conversion rates and revenue among tech-savvy consumers Financial service companies are using AI to price assets, analyze risk, offer new services, and provide new customer experiences.